STRUKTUR DAN PROSES MEMORI - Magda Bhinnety (Buletin Psikologi, 2008)
This paper describes structures and processes of human memory system according to the modal model. Sensory memory is described as the first system to store information from outside world. Short‐term memory, or now called working memory, represents a system characterized by limited ability in storing as well as retrieving information. Long‐term memory on the hand stores information larger in amount and longer than short‐term memory